PENINGKATKAN POTENSI DESA MELALUI PEMBERDAYAAN MASYARAKAT DENGAN MEMANFAATKAN LIMBAH DI DESA KADINGEH - Andini, Andini; Robertinus, Robertinus; Setiawan, Asep (Nindikayla Institute, 2022)
Waste is often interpreted as something that has no benefits so that waste is often just thrown away. Without us realizing it, there is actually a lot of waste that actually has benefits when we know how to process it. Many people think that livestock manure is waste that cannot be processed, so many people just leave it alone. Through the processing of livestock manure, it can become something that has high value among the community, especially in the agricultural world, because livestock manure can be used as organic fertilizer for plants. Therefore, the UM PAREPARE KKN Team, Batch XXIII 2021 Group 55 Conducted training on making organic fertilizer/compost in Kadingeh village, kec. Baraka, district. Enrekang, as a form of service as well as to increase the potential of the village. After the training was held on August 26, 2021, the people of Kadingeh village already understood how to manage livestock dung waste into organic fertilizer/compost